Penyuluhan Etika dan Dampak Psikologis Media Sosial dalam Perspektif Agama Kristen untuk Siswa SMTK Soe Kabupaten Timor Tengah Selatan: Penyuluhan Etika dan Dampak Psikologis Media Sosial dalam Perspektif Agama Kristen untuk Siswa SMTK Soe Kabupaten Timor Tengah Selatan - Messakh, Merling T.L.L.C; Daik, Irene Elvira; Kale, Eko Paulus; Mayok, Jemris I.D; Liunokas , Mazdad (Institut Agama Kristen Negeri Kupang, 2025)
Teenagers' lives are inseparable from social media in this digital era. Diverse platforms like Instagram, TikTok, and Facebook offer unlimited connectivity and rapid access to information. However, social media use also brings new challenges, particularly in terms of ethics and psychological impacts. Teenagers, as active social media users, often face dynamic decision-making and psychological issues. Students of SMTK Soe in South Central Timor Regency, who are part of the digital generation, are not immune to this phenomenon. Students spend 3-12 hours a day, lack sleep, are unable to focus on learning, are anxious because they compare their lives to idols or influencers, and are involved in cyberbullying. Therefore, counseling on leadership, ethics, and the psychological impact of social media from a Christian perspective is highly relevant and important for students to be able to manage social media responsibly. Based on the problems found by Community Service partners, the PKM team prepared a counseling activity with the theme Psycho-Social Media: Counseling on Ethics and Psychological Impacts of Social Media in a Christian Perspective for Students of SMTK Soe, South Central Timor Regency to answer Partners' problems. The seminar was delivered to 30 students of SMTK Soe City on November 26, 2024 with 3 sessions, namely the Use of Social Media from a Christian Leader's Perspective, the Psychological Impact of Social Media for Teenagers with Biblical Principles, and Social Media Ethics. The delivery of material using interactive learning methods such as group discussions, case studies, and simulations can help students to more easily understand and internalize Christian values ??in the context of social media use. After the presentation of the material, students made a commitment card for positive and beneficial use of social media so that they could make decisions to use social media positively and avoid the negative impacts of social media use. Keywords: Ethics Education; Psychological Impact; Social Media